Rancang Bangun Sistem Pendaftaran Peserta Didik Baru (PPDB) Berbasis Website Di RA Khairul Ummah Dengan Metode Waterfall - Gajah, Handika; Febiola, Kintan; Fajriah, Nursyamsiah; Ilham, Farizi (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
The rapid advancement of technology has significantly impacted various sectors, including education. One area affected by this digital shift is the administrative process of student registration. This report discusses the design and development of a web-based system for new student registration (PPDB) at RA Khairul Ummah, aimed at replacing the inefficient and time-consuming manual registration process. The system was developed using the Waterfall method, which includes requirements analysis, system design, implementation, testing, and maintenance. PHP was used for server-side programming, while MySQL was applied as the database management system. The system allows prospective students to register online, upload required documents, and track registration status in real-time. The implementation of this system significantly improves efficiency, data accuracy, and reduces processing time. Additionally, it simplifies the management of registrations and broadens the reach of information. This project helps RA Khairul Ummah adapt to the digital era and is expected to inspire other educational institutions to adopt similar digital solutions.